The Japan-South Korea identity clash : East Asian Security and the United States - Glosserman, Brad; Snyder, Scott, 1964- (Contemporary Asia in the world., 2015)
Japan and South Korea are Western-style democracies with open-market economies committed to the rule of law. They are also US allies. However, despite their shared interests, shared values, and geographic proximity, divergent national identities have driven a wedge between them. Drawing on decades of expertise, Brad Glosserman and Scott Snyder investigate the roots of this split and its ongoing threat to the region and the world.